A Critical Review of AI Chatbots as Interactive Media for Arabic Language Learning: Integrating Explainable AI and the Cognitive Theory of Multimedia Learning - Gufron Zainal Abidin Sdawi Manasiq; Abd Ghani (CV Alifba Media, 2024)
This study investigates the pedagogical limitations of AI chatbots in Arabic language learning, particularly the lack of integration of Explainable AI and the Cognitive Theory of Multimedia Learning (CTML). The aim is to develop a theoretical framework that promotes cognitive alignment and instructional transparency. A qualitative, library-based method was used, analyzing academic literature on Arabic instruction, AI systems, and multimedia learning. Findings reveal that current chatbot designs often neglect cognitive load and offer limited explanation of responses. As a result, learner trust and comprehension suffer. The study concludes that integrating CTML and Explainable AI can enhance the effectiveness, trustworthiness, and cognitive depth of chatbots in Arabic language education.